An Application of Ulam-Hyers Stability in DC Motors - Abasalt Bodaghi; Naser Pargali (Institute of Advanced Engineering and Science, 2014)
In this paper, a generalization to nonlinear systems is proposed and applied to the motor dynamic, rotor model and stator model in DC motor equation. We argue that Ulam-Hyers stability concept is quite significant in design problems and in design analysis for the class of DC motor’s parameters. We prove the stability of nonlinear partial differential equation by using Banach’s contraction principle. As an application, the Ulam-Hyers stability of DC motor dynamics equations is investigated. To the best of our knowledge this is the first time Ulam-Hyers stability is considered from the applications point of view.